Michigan's recent school finance reforms: A preliminary report - Loeb, Susanna; Courant, Paul N.; Grämlich, Edward M. (American Economic Review, 1995)
Historically, Michigan has relied more heavily than most other states on local taxes and property taxes as sources of education finance. In the 1990-1991 school year, Michigan was third among states in the share of school spending financed locally (65.2 percent).1 Over the past two decades there have been more than ten propertytax-cut initiatives placed on statewide ballots. In the summer of 1993 the legislature passed a bill that abolished, with no source of revenue replacement specified, all use of local property taxes (at the time, over $6 billion) for school operating expenditures. In late December, both houses passed, and the governor signed, a financing bill that contained two options for voters to choose from, either of which would have replaced approximately all of the lost revenue. Here are the main provisions of the new system, as passed by the voters in March, 1994: (i) a combination of an increased state sales tax, a statewide property tax on all property, a (nearly) required local property tax on nonhomestead property,2 a sharp increase in the tobacco tax, and a real-estate transfer tax; (ii) a system of state foundation grants to school districts that would, when fully implemented, put a floor under spending of $5,000 per pupil in 1994-1995, while preserving nominal differences in spending per pupil among districts that currently spend $5,000 per pupil or more; (iii) strengthened requirements for an academic core curriculum, pupil performance standards, and minimum numbers of school days; (iv) provisions for authorizing charter schools, schools of choice that would be subject to the statewide curriculum and testing requirements but would not have to use certified teachers. (A Michigan court ruled these schools unconstitutional, but the legislature has since rewritten the law to meet the court's objections.) Thus, the new law switched Michigan from a modified powerequalization system to a modified foundation system.